Theoretical Study on Highly Active Bifunctional Metalloporphyrin Catalysts for the Coupling Reaction of Epoxides with Carbon Dioxide. Issue 5 (16th June 2016) - Hasegawa, Jun‐ya; Miyazaki, Ray; Maeda, Chihiro; Ema, Tadashi
Abstract: Highly active bifunctional metalloporphyrin catalysts were developed for the coupling reaction of epoxides with CO2 to produce cyclic carbonates. The bifunctional catalysts have both quaternary ammonium halide groups and a metal center. To elucidate the roles of these catalytic groups, DFT calculations were performed. Control reactions using tetrabutylammonium halide as a catalyst were also investigated for comparison. In the present article, the results of our computational studies are overviewed. The computational results are consistent with the experimental data and are useful for elucidating the structure–activity relationship. The key features responsible for the high catalytic activity of the bifunctional catalysts are as follows: 1) the cooperative action of the halide anion (nucleophile) and the metal center (Lewis acid); 2) the near‐attack conformation, leading to the efficient opening of the epoxide ring in the rate‐determining step; and 3) the conformational change of the quaternary ammonium cation to stabilize various anionic species generated during catalysis, in addition to the robustness (thermostability) of the catalysts. Abstract : Highly active bifunctional metalloporphyrin catalysts were developed for the reactions of epoxides with CO2 to produce cyclic carbonates. The bifunctional catalysts have the metal center and the quaternary ammonium halide. DFT calculations were performed to elucidate the reaction mechanism. The results were consistent with the experimental data and useful for understanding the structure–activity relationship.